2019
DOI: 10.1001/jamapediatrics.2019.3826
|View full text |Cite|
|
Sign up to set email alerts
|

National Prevalence of Pain Among Children and Adolescents With Autism Spectrum Disorders

Abstract: Drs Bettis and Liu had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 5 publications
1
32
1
Order By: Relevance
“…For the first time, a relation between symptoms of autism spectrum disease (ASD) and pain in DM1 is investigated. In previous pain studies on individuals diagnosed with autism, both hypo-and hypersensitivity are reported [69,70]. Whether the correlation between pain and ASD symptoms identified in the current study are due to a common cause, or a result of abnormal selfreporting in individuals with high rates of ASD symptoms, is not known.…”
Section: Pain and Gendermentioning
confidence: 67%
“…For the first time, a relation between symptoms of autism spectrum disease (ASD) and pain in DM1 is investigated. In previous pain studies on individuals diagnosed with autism, both hypo-and hypersensitivity are reported [69,70]. Whether the correlation between pain and ASD symptoms identified in the current study are due to a common cause, or a result of abnormal selfreporting in individuals with high rates of ASD symptoms, is not known.…”
Section: Pain and Gendermentioning
confidence: 67%
“… 51 In fact, empirical studies of pain in ASD tend to report increased pain sensitivity 57 and our work adds more data that challenge these old assumptions. Also, because many individuals with ASD have a number of comorbid medical conditions that could cause or exacerbate pain, 18 , 61 accurate assessment and management of pain is imperative in this population.…”
Section: Discussionmentioning
confidence: 99%
“… 53 There is a paucity of empirical pain research in ASD, yet recent data suggest children with ASD experience more painful conditions compared to their peers. 61 Complicating pain assessment in ASD is the fact that verbal, self-report of pain is still the “gold standard,” thus, for individuals with ASD or similar communication difficulties, accurate assessment of pain can be challenging. As pain is a complex sensory, emotional, and social experience, 12 there are many possible reasons for altered pain behaviors and responses in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 90% of ASD toddlers are unable to point protodeclaratively or protoimperatively (16). Indeed, many individuals with ASD are incapable of pointing to the source of their discomfort, find it difficult to attend to or detect bodily sensations (17), have poor integration of body scheme representation, and have atypical sensory perceptions or reports of pain (18). This inability to communicate pain or discomfort to other people may propitiate the enactment of inappropriate behaviors as a way for patients to express themselves and attract attention to their plight.…”
Section: Comorbidity and Autism Spectrum Disordermentioning
confidence: 99%